Digital Gaming and Sustainable Design - Vassigh, Shahin (Enquiry The ARCC Journal for Architectural Research, 2008)
The American building industry is one of the major consumers of energy. Buildings use 39% of thetotal energy consumed in the United States, significantly impacting national energy demand andcontributing to global warming. The vast majority of architectural practice in US leads to construction of buildings with a little concern to sustainability leading to environmental degradation. Although the bulk of architecture practice continues to produce unsustainable buildings, there is growing stream of exemplary models of sustainable design. Examining the success of suchpractices leads into two a two-folded finding; first that achieving sustainable design is closelylinked to "integrated Design”1 - a type of practice in which various disciplines involved in building design work together to achieve efficiency and other synergetic benefits. Second is that theadvances in computing and simulation algorithms are paving the way to achieve "integrateddesign”. These technologies are enabling the designers to collaborate, visualize, foresee, andmodify building performance with relatively high accuracy. They are increasing used to analyze complex systems to achieve streamlined structures, reduce dependence on mechanical systems, produce more effective construction processes, and reduce waste.If such practices were to become widespread, the architectural education needs to be restructured.The traditional American architectural curriculum that is based on a schism between"design” and "technology” is inherently in conflict with the principal of integration. Though largescalereform of architectural curricula is a complex, ongoing, and difficult debate; producing teaching tools that can simulate integrated design can impact and promote an understanding of sustainable practice in architecture. The proposed paper will present the progress of a multi-disciplinary team of faculty who arecollectively working on the completion, implementation and evaluation of a simulation softwarepackage in an interactive game format. The project teaches the concepts of "integrated design ”through immersing students in a virtual world that imitates the complexity of the real world of decision-making and material choices in design. The project accomplishes this by harnessingthe capabilities of simulation and dynamic modeling programs as well as powerful game engineswhile creating compelling and rewarding reasons for student’s engagement in the learning process. The project is funded by the US Department of Education for the period of 2007-2010.